Sorption mechanisms of diethyl phthalate by nutshell biochar derived at different pyrolysis temperature. Issue 2 (April 2022) - Fan, Xinhui; Wang, Xiaoqing; Zhao, Bin; Wan, Junfeng; Tang, Jianwei; Guo, Xiaoying
Abstract: The sorption properties of diethyl phthalate (DEP) by four series of biochar samples produced from apricot shell, coconut shell, peanut shell and walnut shell at 300–800 ℃ were investigated. The morphology, physical structure and chemical composition of biochar were characterized by SEM, N2 and CO2 adsorption-desorption isotherms, elemental analysis, 13 C NMR, FTIR and TGA, showing that with the increase of pyrolysis temperature, the yield and polarity of biochar decreased, while the aromaticity increased. All the sorption isotherms were fitted by Freundlich model and exhibited highly nonlinear with n ranging from 0.16 to 0.55. Compared with higher-temperature biochar (HBCs, 500–700 ℃), the lower-temperature biochar (LBCs, ≤ 400 ℃) had stronger sorption intensity in each series due to specific interaction (e.g. hydrogen bonding) between the polar functional groups in LBCs (ASBs, WSBs and PSBs) and DEP molecules. Differently, the sorption interactions between HBCs and DEP were mainly driven by the surface adsorption at the energy sites and the 800 ℃-derived biochars with high specific surface area (415.13–454.17 m 2 /g) were the strongest in the same series. Peanut shell derived-biochar with higher K oc ( C e =0.1 S w ) values of 358–3670 L/kg had excellent sorption performance, suggesting its promising potential for remediation of DEP in the environment. Capsule: The underlying sorption mechanisms of diethyl phthalate (DEP) by four series of nutshell biochar derived at different pyrolysis temperature (300–800 ℃) were investigated. Graphical Abstract: ga1 Highlights: LBCs (≤ 400 ℃) showed stronger sorption than HBCs (500–700 ℃) except for CSBs. All 800 ℃ biochar had highest surface area and strongest sorption intensity for DEP. The sorption of most LBCs (≤ 400 ℃) was mainly regulated by polar interactions. The sorption of HBCs (≥500 ℃) was mainly driven by the surface adsorption. Peanut shell-derived biochar (PSBs) showed promising potential for remediation.